A cream containing the sap of oat plantlets and mandarin extract soothes the symptoms of rosacea and improves the quality of life of patients. (7th July 2022) - Fabbrocini, G.; Monteil, C. Beziat; Carballido, F.
Abstract: Background: Rosacea is a chronic inflammatory disease of the facial skin that affects all skin types and occurs mostly in adults. The main clinical sign of rosacea is a characteristic and persistent form of centro‐facial erythema that is prone to exacerbation and can impair quality of life (QoL). The current therapeutic approach for rosacea is to combine various treatments, use appropriate skincare products and avoid flare‐up triggers. Objective: To evaluate the use of a facial skincare product containing protein‐free sap extruded from Rhealba® oat plantlets and mandarin extract in subjects with rosacea. Methods: Three clinical studies were conducted in adult subjects with various rosacea phenotypes (erythematotelangiectatic or papulopustular) and treatment histories to assess the dermatological and ophthalmological tolerance of the study product, as well as its clinical effectiveness, after a twice‐daily application on the whole face and neck for up to 4 weeks. Results: Tolerance of the product was rated as good to very good by dermatologists across the three studies, which involved a total of 105 evaluable subjects. Subjects with untreated erythematotelangiectatic rosacea reported fewer functional signs and symptoms of the disease and an improved QoL. The evaluation of skin biometric parameters revealed a reduction in transepidermal water loss, indicating that the study product helped to restore skin barrier integrity after 4 weeks, and a higher skin pH, indicating that the cutaneous microbiote was respected. Most subjects (93%) who had either undergone a superficial dermatological procedure for erythematotelangiectatic rosacea or were taking oral/topical treatments for papulopustular rosacea, rated the study product as very good (8/10) and felt it further relieved their symptoms. Conclusion: Overall, the study product was very well tolerated and may be beneficial for subjects with rosacea as an adjunct to superficial dermatological procedures or oral/topical therapies, in line with the current recommendations for rosacea management.